Human Resource Management Practices and Organizational Performance: Study in Sudan National Oil Company (SNOC) - Ali, Abu Bakr Ali Abd Ellatif (2011)
This study investigates the impact of HRM practices on organizational performance which include practices such as "human resource planning, staffing processes, training and development, reward and compensation systems, employee and labor relations", and are treated as independent variables. The study is concentrating on study on Sudan National Oil Company (SNOC). Total responses are 100 from 153 population of Sudan National Oil Company (SNOC) are collected and analyzed objectively; it was examined if HRM practices have significant association on organizational performance. The aim is to get real picture on the influence of HRM practices on organizational performance. The finding indicates that, there is positive relationship between HRM practices and organizational performance. This study is important for several reasons. Firstly, recognizing a positive relationship between, HRM and organizational performance; secondly, to clarify the problem and barriers encountered in the application of human resource programs in the Sudanese companies in the context to the case included in this study thirdly, to participate in and contribute to research, resulting in Knowledge increase, and lastly, to assist scholars and other researchers in the HRM field.